ANALISIS PENGUKURAN KINERJA DENGAN MENGGUNAKAN BALANCE SCORECARD PADA SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) BATUSANGKAR - Yenti, Elfina; Fitri, Sri Adella (JURIS (Jurnal Ilmiah Syariah), 2014)
Balanced Scorecard was not only used as a tool for measuring the successful of a company, but also as a total strategic transformation for all levels of a company organization. The successful comprehensive measurement could be done by combining finance and non-finance source, so that the company could measure its success well. Based on Undang-Undang Republik Indonesia No. 9 th. 2009 about ‘Badan Hukum Pendidikan’, educational institution should be handled optimally like an industry in order that they had to be able to compete with other companies. The main point was that an university as one of educational institution had to improve and protect its quality: graduates, costs, services, and human resources.